Rancang Bangun Sistem Informasi Pengarsipan Surat Berbasis Web Menggunakan Framework Codeigniter Di Ponpes At-Tajdid Muhammadiyah Tasikmalaya - Rifqi Aminullah; Milah Nurkamilah; Sulidar Fitri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Archiving letters and administrative documents plays an important role in the operational activities of an educational institution. However, many educational institutions, including At-Tajdid Muhammadiyah Tasikmalaya, face challenges in manual archiving, which is time-consuming and prone to errors. This study aims to address these issues by developing a Web-Based Letter Archiving Information System using the CodeIgniter framework at At-Tajdid Muhammadiyah Tasikmalaya. This research adopts the Extreme Programming (XP) approach in the system development process. The main objective is to create a solution to overcome the problems of manual letter archiving. By designing and implementing a web-based information system, it is expected to simplify the archiving process, reduce human errors, and improve efficiency and accuracy in data retrieval. The expected outcome of this research is the design and implementation of a Web-Based Letter Archiving Information System at At-Tajdid Muhammadiyah Tasikmalaya. This system will replace the conventional archiving process with a digital method that utilizes the latest information technology. By using the CodeIgniter framework, the system will provide better accessibility.